Effects of aminooxyacetic acid and sugar on the longevity of pollinated Dendrobium Pompadour - Zuliana, R.; Boyce, A.N.; Nair, H.; Chandran, S. (2008)
Experiments were carried out to investigate the effects of different types and concentration of sugars and Aminooxyacetic acid (AOA) and a combination of both sugar and AOA in extending the vase lives of pollinated Dendrobium Pompadour flowers. Post pollination symptoms such as weight loss, water uptake, petal thickness and discoloration were monitored. The results obtained showed that the most effective treatments in extending the vase life of pollinated Dendrobium Pompadour flowers and delaying the post pollination symptoms were 0.05 mM AOA and the treatment which combined 0.05 mM AOA with 4 glucose. Both treatments showed a longer vase life than that of the control. Furthermore positive effects were also observed in a delay of weight loss, improved water uptake, change in thickness and colour. A combination of 0.05 mM AOA and 2 sucrose extended the vase life of flowers up to 5 days. Inclusion of 4 glucose and 2 sucrose alone only prolonged the vase life of flowers two days more compared to that of the control. Holding solutions containing sugars alone maintained pH values of 5-7 while solutions containing AOA and a combination of AOA and sugars showed more acidic values of pH of 3-5 throughout. AOA and a combination of AOA and glucose can therefore extend the vase life of pollinated Dendrobium Pompadour flowers and also delay the post pollination syndrome. Â© 2008 Asian Network for Scientific Information.